Broken Voices Postcolonial Entanglements and the Preservation of Korea's Central Folksong Traditions - Maliangkay, Roald (Music and Performing Arts of Asia and the Pacific, 2017)
'Broken Voices' is the first English-language book on Korea's rich folksong heritage, and the first major study of the effects of Japanese colonialism on the intangible heritage of its former colony. In 2009, many Koreans reacted with dismay when China officially recognized the folksong 'Arirang', commonly regarded as the national folksong in North and South Korea, as part of its national intangible cultural heritage. They were vindicated when versions from both sides of the DMZ were included in UNESCO's Representative List of the Intangible Cultural Heritage of Humanity a few years later. At least on a national level, folksongs thus carry significant political importance. Maliangkay describes how an elaborate system of heritage management was first established in modern Korea and raises an important issue of cultural preservation-traditions that fail to attract practitioners and audiences are unsustainable, so compromises may be unwelcome but imperative.